Implementasi E-Modul Praktikum Statistika dalam Riset Keagamaan: Dampaknya terhadap Kesiapan Mahasiswa - Indriani, Tari; Wahyudhi, Syukron; Diansyah, Refor; Resvan; Purnamasari, Wulan (CV Global Research Publication, 2026)
This research stems from students' low skills in the socio-religious field in conducting statistical analysis and the limited independence of learning due to the lack of contextual and applicable learning resources. Statistics learning, which tends to be theoretical and time-limited, also contributes to the gap between conceptual mastery and practical skills. Therefore, the purpose of this study is to describe the application of the statistics practicum e-module in socio-religious research and its impact on students' readiness as prospective research assistants. The method used in this study is a quantitative approach with a descriptive quantitative research type. The research respondents consisted of 30 sixth-semester students of the Da'wah Management Study Program selected using a purposive sampling technique. Data were collected through a questionnaire with a Likert scale of 1-4, then processed using descriptive statistical methods and presented in tabular form. The results of the study indicate that the statistics practicum e-module received a positive response from students in all assessment aspects, with a predominance of the